2012
DOI: 10.1126/science.1219631
|View full text |Cite
|
Sign up to set email alerts
|

The Tides of Titan

Abstract: We have detected in Cassini spacecraft data the signature of the periodic tidal stresses within Titan, driven by the eccentricity (e = 0.028) of its 16-day orbit around Saturn. Precise measurements of the acceleration of Cassini during six close flybys between 2006 and 2011 have revealed that Titan responds to the variable tidal field exerted by Saturn with periodic changes of its quadrupole gravity, at about 4% of the static value. Two independent determinations of the corresponding degree-2 Love number yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
181
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 260 publications
(198 citation statements)
references
References 15 publications
11
181
0
Order By: Relevance
“…2d). Measured tidal fluctuations in the gravity field are consistent with the existence of a decoupling water layer below the ice shell (Iess et al, 2012). The interpretation of gravity and topography data indicate that the thickness of the ice shell above the ocean should vary with latitude and longitude, implying that the ice shell is thermally conductive and has a high viscosity at present (Hemingway et al, 2013;Lefevre et al, 2014;Mitri et al, 2014).…”
supporting
confidence: 56%
“…2d). Measured tidal fluctuations in the gravity field are consistent with the existence of a decoupling water layer below the ice shell (Iess et al, 2012). The interpretation of gravity and topography data indicate that the thickness of the ice shell above the ocean should vary with latitude and longitude, implying that the ice shell is thermally conductive and has a high viscosity at present (Hemingway et al, 2013;Lefevre et al, 2014;Mitri et al, 2014).…”
supporting
confidence: 56%
“…Note that e=0.03 is significantly larger than the eccentricities of the Galilean satellites, but approaches that of Titan (e=0.028; Iess et al 2012). Owing to their position within a circumplanetary disk, we expect that any young moons will possess eccentricities at least as small as the Galilean satellites and ought therefore to be captured in the adiabatic regime.…”
Section: Capture Into Resonancementioning
confidence: 95%
“…For the remaining 32 min while the Huygens gondola was staying at rest on the surface until the end of telemetry link, the statistical analysis of the signal to noise ratio (SNR) revealed that there is more than a 50% chance for a 36 Hz SR signal being permanently present at the surface. Besides these direct indices in favor of the presence of that signal during nearly 3 h of Huygens data transmission, the constraints on the structure of the SR cavity derived from the spectral characteristics of the 36 Hz signal allowed to predict the presence of a conductive ocean, buried 50-60 km underneath the icy-crust (Béghin et al, 2010), that was furthermore confirmed by the tidal variations of Titan's gravity field (Iess et al, 2012).…”
Section: Discussionmentioning
confidence: 91%